Sustainable Development and Corporate Sustainability of Chilean State Universities: Evidence from Their Strategic Elements - Abello-Romero, J (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Corporate sustainability evolved in line with the advancement of the concept of sustainable development; thus, it is constituted as a strategy to respond to social and environmental problems. In this context, universities are understood as complex organizations, positioned as a key mechanism for delivering the sustainable development of society. This research aimed to analyze whether the strategic elements of Chilean state universities integrate components of sustainable development. For this purpose, qualitative research was undertaken through a documentary analysis of the strategic plans of the 18 Chilean state universities, focusing analysis on their strategic elements: their mission, vision and strategic institutional objectives. The results revealed that all universities mention at least one concept associated with one of the 17 Sustainable Development Goals (SDGs) in their strategic guidelines. They mainly focused on ‘Quality Education’ (SDG 4) and ‘Build resilient infrastructure, promoting inclusive and sustainable industrialization and foster innovation’ (SDG 9). Also, the results allow us to visualize how universities address corporate sustainability issues through their strategic plans. © 2023 by the authors.